Karakteristik Pemanfaatan Pohon oleh Jalak Bali (Leucopsar Rothschildi) di Taman Nasional Bali Barat Wilayah SPTN III, Buleleng, Bali - Aryanti, Nirmala Ayu; Wicaksono, Reyza Hermawan (Biotropika: Journal of Tropical Biology, 2018)
Leucopsar rothschildi (Jalak Bali) is an endemic bird species that only be found in the forests of the western of Bali Island. Wild catching and declining forest are the main factors of the declining population. The National Park of West Bali is the last bastion. The habit of living for activity and nesting in the trees make the importance of tree stand to be preserved. Therefore, this study was conducted to analyze the utilizations characteristics of trees by the birds in their original habitat in SPTN III West Bali National Park. The method used was concentration count to observe the characteristics utilization of trees and canopy. Behavior in their natural habitat was observed using Ad Libitum method. Data analysis was conducted by calculating percentage in each part of the usage of canopy and behavior type. The use of the canopy of trees in SPTN III of Labuhan Lalang TNBB by the birds for Tanjung Gelap was more frequent in the upper canopy (TA) section, in Labuhan Lalang more often in the middle canopy (TT) and the middle side canopy (TTt). Frequently activity in the canopy of SPTN III Labuhan Lalang by the birds was social activity.